2007
DOI: 10.1111/j.1600-0501.2006.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic evaluation of implant‐supported prostheses in hemimandibulectomy‐reconstructed patients

Abstract: Post-rehabilitation median scores of the questionnaire indicated a positive judgment of the treatment. EMG analysis showed that functional recovery in hemimandibulectomy patients was satisfactory, although some alterations were observed in the non-operated side of mastication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
(62 reference statements)
1
9
0
2
Order By: Relevance
“…Interestingly, however, the standardised global Impact displayed different intergroup values during our chewing test. In the current reference subjects, pooled and working‐side muscular activities were comparable with data from previous studies on healthy dentate control individuals, independently from age . The present patients with All‐on‐Four ® prostheses on both dental arches had no significantly different global Impact from that of control subjects, whereas patients wearing a maxillary denture showed double values of Impact than reference subjects.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, however, the standardised global Impact displayed different intergroup values during our chewing test. In the current reference subjects, pooled and working‐side muscular activities were comparable with data from previous studies on healthy dentate control individuals, independently from age . The present patients with All‐on‐Four ® prostheses on both dental arches had no significantly different global Impact from that of control subjects, whereas patients wearing a maxillary denture showed double values of Impact than reference subjects.…”
Section: Discussionmentioning
confidence: 93%
“…Electromyographic activity was recorded during a 15 s unilateral (left and right) chewing of sugarless gum, and the potentials produced were standardised as detailed before. From the EMG potentials recorded from the four tested muscles during each chewing test, the following parameters were computed: the masticatory frequency, resulting as the number of cycles/time; the global masticatory Impact Coefficient (IC,%), computed as in MVC; the working‐side Impact Coefficient (W‐IC,%), computed as the percentage of the pooled muscle activity developed on the working side; the Impact per cycle (IC/cycle,%), calculated as the Impact/number of chewing cycles; the area of the confidence ellipse of the simultaneous differential left–right MM and TA activity (Lissajous plot, ). The confidence ellipse is a statistic computed to assess the repeatability of the masticatory muscle pattern of contraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the aim of this study was to assess information on bite force, QoL, and SEMG during the rehabilitation process of edentulous individuals, replacing their conventional dentures for mandibular implant-supported dentures to assess whether this procedure would benefit them before the new dentures were installed. Different authors have reported results before and after the treatment realization, but none of them collected data during the clinical conduct (Mericske-Stern 1994; Bakke et al 2002;Dellavia et al 2007;Berretin-Felix et al 2008;Emami et al 2009Emami et al , 2015Caloss et al 2011;da Silva et al 2011;Dakhilalian et al 2012Dakhilalian et al , 2014Fatalla et al 2012;Geckili et al 2012b;Mumcu et al 2012;Preciado et al 2012;Awad et al 2014;Cakir et al 2014;De Rossi et al 2014;Boven et al 2015;Mundt et al 2015;Shaghaghian et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Niektóre urządzenia, takie jak system diagnostyczny K7 CMS (Myotronics, Noromed, USA) pozwalają na wykonanie elektronicznej rejestracji ruchów żuchwy, elektromiografii oraz elektrosonografii pozwalając na kompleksową analizę układu ruchowego narządu żucia. Elektromiografia powierzchniowa stosowana była również w celu oceny aktywności mięśni po podścieleniu protez (10) lub rekonstrukcji żuchwy po operacji hemimandibulektomii (11).…”
unclassified